2023
DOI: 10.3390/fermentation9100898
|View full text |Cite
|
Sign up to set email alerts
|

Syngas Fermentation: Cleaning of Syngas as a Critical Stage in Fermentation Performance

Marcos Ellacuriaga,
María Victoria Gil,
Xiomar Gómez

Abstract: The fermentation of syngas is an attractive technology that can be integrated with gasification of lignocellulosic biomass. The coupling of these two technologies allows for treating a great variety of raw materials. Lignin usually hinders microbial fermentations; thus, the thermal decomposition of the whole material into small molecules allows for the production of fuels and other types of molecules using syngas as substrate, a process performed at mild conditions. Syngas contains mainly hydrogen, carbon mono… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 221 publications
0
4
0
Order By: Relevance
“…Therefore, other technologies would need to get into play as it would be biomass gasification of forestry material and lignocellulosic wastes [39]. However, gasification technology has to overcome several challenges regarding syngas cleaning, tar production and char quality along with inefficiencies caused by biomass transport logistics and energy densification [40,41].…”
Section: Biogas Syngas and Syngas Derivatesmentioning
confidence: 99%
“…Therefore, other technologies would need to get into play as it would be biomass gasification of forestry material and lignocellulosic wastes [39]. However, gasification technology has to overcome several challenges regarding syngas cleaning, tar production and char quality along with inefficiencies caused by biomass transport logistics and energy densification [40,41].…”
Section: Biogas Syngas and Syngas Derivatesmentioning
confidence: 99%
“…For instance, a recent study demonstrated the feasibility of using syngas generated by the gasification of biogenic residues as a substrate for fermentation to produce short- and medium-chain alcohols using the acetogenic bacterium Clostridium carboxidivorans [ 105 ]. Syngas production (mainly derived from lignocellulosic biomass) and fermentation for microbial conversion of gaseous substrates to various products have been well reviewed in the literature [ 106 , 107 , 108 ].…”
Section: Integrated Biorefinery Approach For a Next-generation Methan...mentioning
confidence: 99%
“…Therefore, other technologies would need to come into play as it would be biomass gasification of forestry material and lignocellulosic wastes [40]. However, gasification technology has to overcome several challenges regarding syngas cleaning, tar production, and char quality along with inefficiencies caused by biomass transport logistics and energy densification [41,42].…”
Section: Biogas Syngas and Syngas Derivatesmentioning
confidence: 99%